Meat food in the traditional gastronomic culture of the Kabardians in the late 19th – early 20th century - Zalina, Balkarova (Kavkazologiya, 2025)
The article is devoted to the study of meat dishes in the traditional gastronomic culture of the Kabardians in the late 19th and early 20th centuries. It provides general information about meat dishes, methods and technologies for preparing meat dishes, as well as information about the variety of meat dishes made from cattle, small livestock, and poultry. Based on the analysis of scientific literature and field materials collected by the staff of the Kabardino-Balkarian Research Institute in the 1950s and 1970s in the villages of Kabardino-Balkaria, the article examines the features of cooking dishes made from lamb and its by-products, goat meat, beef, and the meat of some other animals. The article draws attention to the widespread use of lamb, beef, and poultry meat in Kabardian cuisine, and also describes the methods of preparing dishes from these ingredients. The study revealed that poultry meat can be classified according to its prestige. It was also found that goat meat dishes were widely used in the traditional gastronomic culture of the Kabardians. It was revealed that most dishes had names in their native language that accurately reflected their semantics and characteristics. It has been established that meat was one of the markers of ethnocultural identity, reflecting one's belonging to one's own people.